A single-dose, randomized, open-label, four-period, crossover equivalence trial comparing the clinical similarity of the proposed biosimilar rupatadine fumarate to reference Wystamm® in healthy Chinese subjects - Lin, Sisi; Lou, Yutao; Hao, Rui; Shao, Yiming; Yu, Jin; Fang, Lu; Bao, Meihua; Yi, Wu; Zhang, Yiwen (Frontiers in Pharmacology, 2024)
The aim of this study was to evaluate the bioequivalence of two formulations of rupatadine (10 mg tablets) under fasting and fed conditions in healthy Chinese subjects.Methods: A total of 72 subjects were randomly assigned to the fasting cohort (n = 36) or fed cohort (n = 36). Each cohort includes 4 single-dose observation periods and 7-day washout intervals.. Blood samples were collected at several timepoints for up to 72 h post-dose. Plasma concentration of rupatadine and the major active metabolites (desloratadine and 3-hydroxydesloratadine) were analyzed by a validated HPLC-MS/MS method. Non-compartmental analysis method was employed to determine the pharmacokinetic parameters. Based on the within-subject standard deviation of the reference formulation, a reference-scaled average bioequivalence or average bioequivalence method was used to evaluate the bioequivalence of the two formulations.In the fasting status, the reference-scaled average bioequivalence method was used to evaluate the bioequivalence of maximum observed rupatadine concentration (Cmax; subject standard deviation >0.294), while the average bioequivalence method was used to evaluate the bioequivalence of area under the rupatadine concentration-time curve from time 0 to the last detectable concentration (AUC0-t) and from time 0 to infinity (AUC0-∞ ). The geometric mean ratio (GMR) of the test/reference for Cmax was 95.91%, and the 95% upper confidence bound was 95.91%. For AUC0-t and AUC0-∞ comparisons, the GMR and 90% confidence interval (CI) were 98.76% (93.88%-103.90%) and 98.71% (93.93%-103.75%), respectively. In the fed status, the subject standard deviation values of Cmax, AUC0-t and AUC0-∞ were all < 0.294; therefore, the average bioequivalence method was used.The GMR and 90% CI for Cmax, AUC0-t, and AUC0-∞ were 101.19% (91.64%-111.74%), 98.80% (94.47%-103.33%), and 98.63% (94.42%-103.03%), respectively. The two-sided 90% CI of GMR for primary pharmacokinetic endpoints of desloratadine and 3-hydroxydesloratadine were also within 80%-125% for each cohort. These results met the bioequivalence criteria for highly variable drugs.All adverse events were mild and transient.: Rupatadine fumarate tablet showed a similar safety profile to reference Wystamm ® (J. Uriach y Compañía, S.A., Spain), and its pharmacokinetic bioequivalence was confirmed in healthy Chinese subjects under fasting and postprandial status. Clinical trial registration: [http://www.chinadrugtrials.org.cn/index.html], identifier [CTR20213217].